Clinical Features, Neuropsychology and Neuroimaging in Bipolar and Borderline Personality Disorder: A Systematic Review of Cross-Diagnostic Studies - Massó Rodriguez, Anna; Hogg, Bridget; Gardoki-Souto, Itxaso; Valiente-Gómez, Alicia; Trabsa, Amira; Mosquera, Dolores; García-Estela, Aitana; Colom, Francesc; Pérez, Victor; Padberg, Frank; Moreno-Alcázar, Ana; Amann, Benedikt Lorenz (Frontiers in Psychiatry, 2021)
Background: Bipolar Disorder (BD) and Borderline Personality Disorder (BPD) have clinically been evolving as separate disorders, though there is still debate on the nosological valence of both conditions, their interaction in terms of co-morbidity or disorder spectrum and their distinct pathophysiology. Objective: The objective of this review is to summarize evidence regarding clinical features, neuropsychological performance and neuroimaging findings from cross-diagnostic studies comparing BD and BPD, to further characterize their complex interplay. Methods: Using PubMed, PsycINFO and TripDataBase, we conducted a systematic literature search based on PRISMA guidelines of studies published from January 1980 to September 2019 which directly compared BD and BPD. Results: A total of 28 studies comparing BD and BPD were included: 19 compared clinical features, 6 neuropsychological performance and 3 neuroimaging abnormalities. Depressive symptoms have an earlier onset in BPD than BD. BD patients present more mixed or manic symptoms, with BD-I differing from BPD in manic phases. BPD patients show more negative attitudes towards others and self, more conflictive interpersonal relationships, and more maladaptive regulation strategies in affective instability with separate pathways. Impulsivity seems more a trait in BPD rather than a state as in BD. Otherwise, BD and BPD overlap in depressive and anxious symptoms, dysphoria, various abnormal temperamental traits, suicidal ideation, and childhood trauma. Both disorders differ and share deficits in neuropsychological and neuroimaging findings. Conclusion: Clinical data provide evidence of overlapping features in both disorders, with most of those symptoms shared being more persistent and intense in BPD. Thus, categorical classifications should be compared to dimensional approaches in transdiagnostic studies investigating BPD features in BD regarding their respective explanatory power for individual trajectories.